Application of Supply Chain Management at Drugs Flow in an Italian Hospital District. Issue 1 (February 2021) - Improta, Giovanni; Scala, Arianna; Trunfio, Teresa Angela; Guizzi, Guido
Abstract: The globalization has pushed to change the organization of every companies, even the hospitals. The principal phenomenon in that period and fundamental today again, has been the Supply Chain Management (SCM), with which the company is no longer seen as an isolated entity but active part in an extremely complex supply network. In fact, the only way to guarantee the competitiveness of businesses in the new world economy is through the cooperation and the integration between customers and suppliers. The present work analyses the drugs flow of three Italian hospital: the Cardarelli Hospital in Campobasso, the Veneziale located in Isernia and the San Timoteo site in Termoli. The data was provided by MOLISE DATA SPA that collected the information from all ASREM with particular interest in the already mentioned hospitals. Particularly, will be highlight, using simulation model, the benefits deriving from the implementation of a new Supply Chain, creating a collaboration along the entire logistics-production chain. Thanks to a more efficient management of drugs will get a reduction of business costs and an improvement of the health services offered.